"New Qing History": An Example of "New Imperialist" History. Issue 1 (2nd January 2016) - Zhiting, Li
EDITOR'S ABSTRACT: Seeing New Qing History as a "malicious attack on a sovereign country" by "Western imperialists, " Li explicitly differentiates between a "wrong" and a "right" perspective on Qing history. In his view, the only legitimate standpoint is one that takes the People's Republic of China's territorial reach and "ethnic unity" as a necessary and natural result of history.